Optimization of protein extraction for slaughtered and non slaughtered broiler chicken meat authentication by biogenic silver nanoparticles interaction - Nahar, Mst Kamrun (Institute of Nano Electronic Engineering, 2016)
The main objective of this research is to differentiate slaughtered and non-slaughtered broiler chicken meat by using biogenic silver nanoparticles. The objectives of this research can be listed as follows: to optimize the protein extraction of slaughtered and non-slaughtered broiler chicken meat; to determine the protein solubility and water content of slaughtered and non-slaughtered broiler chicken meat; to synthesis the silver nanoparticles by a biological method from selected plant; to evaluate the protein-biogenic silver nanoparticles interaction in slaughtered and non-slaughtered broiler chicken meat.